STUDY THE HARDNESS AND FIRMNESS INDEXES OF THIN LAMELLATE KNIVES - Urinov Nasillo Fayzilloevich; Sokhibov Ibodullo Adizmurodovich; Amonov Mahmud Idris Ugli (Galaxy International Interdisciplinary Research Journal, 2021)
The article covers technological stability of thin lamellar knives in terms of accuracy in size and shape of cut blanks, identifies main reasons for the deviation of the cutting edge from the cutting plane, structural diagram of lateral deviation of lamellar knife and experimental setup have been developed.